Development of strategies to enhance prevention of preterm labour in the selected hospitals in Capricorn District, Limpopo Province - Makakaba, Gloria Meliddah (My University, 2022)
Background Despite all the interventions that have been developed previously preterm labour remain to be the leading cause of perinatal morbidity and mortality worldwide. Preterm labour occurs before 37 weeks of gestation under two obstetric circumstances namely, ‗spontaneous preterm labour‘ and ‗indicated preterm labour‘. The aim of the study was to develop the strategies to enhance prevention of preterm labour in selected hospitals in Capricorn District, Limpopo Province. Research Method A sequential explanatory mixed method was adopted, the study was conducted in three phases, namely, quantitative study, qualitative study, and development of strategies. Self-developed questionnaires with 50 item questions each for mothers and registered midwives were administered. Both questionnaires were pre-tested prior to being administered to the respondents of the main study. The sample size of mothers was 77 mothers and 62 registered midwives. Data collected from the respondents were analysed using Statistical Package for Social Science (SPSS) version 25 with the help of the statistician. Tables, pie charts and bar graphs were drawn to present the results. The results of quantitative phase were utilized to formulate the Interview Guides that were used to explore the knowledge and practise of registered midwives and obstetricians regarding preterm labour. Interviews were conducted with 20 mothers, 6 registered midwives and 4 obstetricians until data saturation was reached. Data were analysed qualitatively using Tesch‘s Open-Coding method. v Quantitative Results The quantitative results for midwives revealed that about 60% of the mothers who had preterm labour were teenagers. Most of the respondents had ‗spontaneous preterm labour‘ and did not have any comorbidities while few had ‗indicated preterm labour‘ and were induced. All 62(100%) of the midwives showed that the facility does not offer an Outreach Programme on the prevention of preterm labour. Themes and Sub-Themes Results Themes and sub-themes were coded manually. Results that emerged from the integration and comparison of quantitative and qualitative results revealed that the mothers who went into preterm labour spontaneously had little information or no health education regarding preterm labour. Developed strategies The following strategies were developed based on the identified factors that might hinders the prevention of preterm labour and after exploring the knowledge and practice of midwives and obstetricians in the selected hospitals, Capricorn District, Limpopo Province. Strategies includes strengthening of BANC Plus, staff establishment, laboratory turnaround time, outreach programmes and improvement of counselling and support services. Recommendations of the Study The recommendation of the study is divided into three groups which includes recommendations for midwives at the PHC and hospital, recommendations for the obstetricians at the hospital and the recommendations for the Department of Health. The midwives to visit schools and community centres at least twice in a month to give information to the woman of childbearing age and reinforce health education on each Antenatal Care visit. The obstetricians to screen all mothers who are at risk of preterm labour for infections, follow up the results and treat the mothers accordingly. The Department of Health should hire enough staff so that quality care can be vi rendered to the pregnant woman at the PHC and hospital. The Department of Health should develop the electronic database, to register all mothers who have a history of preterm labour, so that when they are pregnant the database system will also help to identify them at the PHC, and they would then be referred to the hospital in time. If the developed strategies to enhance prevention of preterm labour may be adopted and adhered to by the midwives and obstetricians, these may help in reduction of high figures of preterm labour in the selected hospitals.
Thesis (M. (Nursing)) -- University of Limpopo, 2022
Keywords: Preterm Labour; Preterm Birth; Mothers; Midwives; Obstetricians.; Prenatal care; Midwives; Premature infants; Pregnant women -- South Africa -- Limpopo; Pregnancy